Penilaian Domain Pengkajian Paripurna Pasien Geriatri (P3G) sebagai Faktor yang Berpengaruh terhadap Kejadian Pneumonia Nosokomial pada Pasien Usia Lanjut yang Dirawat di Rumah Sakit Umum Pusat Nasional Dr. Cipto Mangunkusumo - Victor, Hildebrand Hanoch; Wahyudi, Edy Rizal; Rumende, C. Martin; Soejono, C. H.; Rooshoeroe, A. G.; Shatri, Hamzah; Nainggolan, Leonard; Irawan, Cosphiadi (UI Scholars Hub, 2023)
Introduction. Nosocomial pneumonia is a lung infection that occurs after the patient is hospitalized for more than 48 hours, without any signs of pulmonary infection at the time of treatment. When compared with young individuals, elderly individuals are more likely to have community-sourced and nosocomial infections with worse outcomes. Comprehensive Geriatric Assessment (CGA) domains are expected to explain the factors that contribute to nosocomial pneumonia in elderly patients. This study aimed to determine the proportion of elderly treated at Dr. Cipto Mangunkusumo National Central General Hospital who experienced nosocomial pneumonia and whether the CGA domains influence the occurrence of nosocomial pneumonia. Methods. A retrospective cohort study was conducted by analyzing the medical records of patients aged 60 years or older who were hospitalized in the medical ward of Geriatric Internal Medicine at Dr. Cipto Mangunkusomo National Central General Hospital in January – September 2019. We also collected secondary data from the geriatric division’s research. The sample consisted of inpatients aged ≥60 years who were hospitalized for more than 48 hours. Those who died within the first 48 hours of hospitalization and subjects with incomplete CGA domain data were excluded from the study. The criteria for nosocomial pneumonia used in this study followed the CDC’s pneumonia criteria for geriatric patients. Data processing was conducted using the application of Statistical Product and Service Solutions (SPSS) 16. Results. Of 228 subjects, the proportion of nosocomial pneumonia in elderly patients hospitalized was 31,14%. The mean age was 69 years with the subject’s age range between 60-89 years. Nutritional status (OR 2.226; CI95% 1.027-4.827) and functional status (OR 3.578; 95%CI 1.398-9.161) are factors that influence the incidence of nosocomial pneumonia in elderly patients who are hospitalized at Dr. Cipto Mangunkusumo National Central General Hospital. Conclusions. The proportion of elderly patients with nosocomial pneumonia was 31.14%. Nutritional status and functional status are factors that influence the incidence of nosocomial pneumonia in elderly patients who are hospitalized at Dr. Cipto Mangunkusumo National Central General Hospital. Keywords: Comprehensive geriatric assessment, elderly, nosocomial pneumonia